2012
DOI: 10.1002/poc.3001
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanisms in flow systems: reduction of SO2 on carbons

Abstract: Surface‐science studies of some reactions have allowed postulating the mechanisms using a variety of techniques. The surface chemistry of Group IV elements has been particularly studied recently because Si, Ge, and C are semiconductors, and the surface organic chemistry to functionalize these elements has seen immense progress in recent years. In this review article we describe the methodology used to study the mechanism of a solid–gas reaction, the reduction of SO2 on carbons, and the necessary conditions tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 95 publications
1
13
0
Order By: Relevance
“…Reduction of SO 2 on carbons to elemental sulfur is an environmentally important reaction to avoid atmospheric pollution. The study of (C + SO 2 ) reaction on different carbons (graphite, charcoal, activated carbon, cokes, and graphene oxide (MPGO)) showed that the reaction proceeds through the same stoichiometry for all carbons (Eqn ), while the reactivity increases with decreasing crystallinity and increasing oxygen content normalSO2+0.25emnormalC0.25emnormalCO2+1/2S2 …”
Section: Introductionmentioning
confidence: 99%
“…Reduction of SO 2 on carbons to elemental sulfur is an environmentally important reaction to avoid atmospheric pollution. The study of (C + SO 2 ) reaction on different carbons (graphite, charcoal, activated carbon, cokes, and graphene oxide (MPGO)) showed that the reaction proceeds through the same stoichiometry for all carbons (Eqn ), while the reactivity increases with decreasing crystallinity and increasing oxygen content normalSO2+0.25emnormalC0.25emnormalCO2+1/2S2 …”
Section: Introductionmentioning
confidence: 99%
“…Figure c shows the peak fitting results of S 2p spectra. It can be divided into four characteristic peaks, including S 2– corresponding to 161.9 eV, S 2 2– corresponding to 162.9 eV, S 0 corresponding to 163.9 eV, and S 6+ corresponding to 168.3 eV. , Among them, S 2– and S 2 2– have at least one lone pair of electrons to interact with Hg 0 , which make them have a high affinity for mercury . Among all sulfur atoms, the atomic ratio of S 2– /S is 0.14 and S 2 2– /S is 0.34, which indicates that the content of FeS 2 in the product is higher than that of FeS and FeS 2 is the main product in the modification process.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Apart from developing porous structures, SO 2 also can be used for further sulfur functionalization. Humeres et al , have systematically investigated the reaction mechanism of SO 2 reduction on carbons as well as the sulfur transport route. It was revealed that SO 2 molecules were first incorporated into the carbon matrix in the form of oxidized sulfur-containing intermediates by interactions with the active sites, and then the oxidized sulfur-containing intermediates decomposed to nonoxidized episulfide intermediates and CO 2 .…”
Section: Results and Discussionmentioning
confidence: 99%